The significant of tourism heritage of Najaf City in Iraq - Akram, Omar Khasro; Ismail, Sumarni; Franco, Daniel Jose (IJETMAS, 2016)
This study adopts the case study of Najaf City, Iraq, to address the problematic of the urban form incorrect transformation and heritage loss. Focusing on the Najaf city, located near to the cities of Baghdad and Babylon, it is an ancient biblical city that was founded in 791 by the Abbasid Caliph HarounAL-Rashid . The city has a large number of historical and heritage values and it’s the destiny for religion purposes, visitors and tourists. However the consecutive changes applied to the urban fabric, due to the lack of regulations and legislation, led to its destruction and to the isolation of the shrines, like the Imam Ali Mosque (PBUH), as buildings not integrated with the rest of the city. There are also present other types of issues regarding the buildings and the projects applied to new structures, where they are not integrated to rest of the city, as well as the buildings deterioration and the lack of maintenance. This paper focus mainly the issues present in the city developments, identifying them, like for instance the skyline changes. As conclusions, it is clear that the several development attempts were not well planed, resulting in a loss of great heritage and heritage values. Restoration and preservation are now processes that must be done in order to present even more losses.